Crotalus durissus ruruima Snake Venom and a Phospholipase A2 Isolated from This Venom Elicit Macrophages to Form Lipid Droplets and Synthesize Inflammatory Lipid Mediators - Ana Eduarda Zulim de Carvalho; Karina Giannotti; Elbio Leiguez Junior; Márcio Matsubara; Maria Cristina Dos Santos; Consuelo Latorre Fortes-Dias; Catarina Teixeira (Journal of Immunology Research)
Viper snake Crotalus durissus ruruima (Cdr) is a subspecies found in northern area of Brazil. Among the snakes of Crotalus genus subspecies, the venom of Cdr presents highest level of crotoxin, which is the major component of Crotalus snake venoms, formed by two subunits (crotapotin and a phospholipase A2 named CBr) and presents potent neurotoxic activity. Curiously, the venom of C. d. ruruima (CdrV) is better neutralized by antibothropic than by anticrotalic serum, strongly suggesting that this venom has similarities with venom of Bothrops genus snakes with regard to the ability to induce inflammation. Macrophages are cells with a central role in inflammatory and immunological responses. Upon inflammatory stimuli, these cells exhibit increased numbers of lipid droplets, which are key organelles in the synthesis and release of inflammatory mediators. However, the effects of CdrV and CBr in macrophage functions are unknown. We herein investigated the ability of CdrV and CBr to activate macrophages with focus on the formation of lipid droplets (LDs), synthesis of lipid mediators, and mechanisms involved in these effects. The involvement of LDs in PGE2 biosynthesis was also assessed. Stimulation of murine macrophages with CdrV and CBr induced an increased number of LDs and release of prostanoids (PGE2, PGD2, and TXB2). Neither CdrV nor CBr induced the expression of COX-1 and COX-2 by macrophages. LDs induced by both CdrV and CBr are associated to PLIN2 recruitment and expression and were shown to be dependent on COX-1, but not COX-2 activity. Moreover, PGE2 colocalized to CdrV- and CBr-induced LDs, revealing the role of these organelles as sites for the synthesis of prostanoids. These results evidence, for the first time, the ability of a whole snake venom to induce formation of LDs and the potential role of these organelles for the production of inflammatory mediators during envenomation by Crotalus snakes.